The NMR Study on Trans-Trans-Dibenzylideneacetone Complex of palladium(II) - Javad Sabounchei, Seyyed; Karamei, Kazem (Asian Journal of Chemistry, 2010)
The complex [(L-L)Pd(dba)], wherse (L-L) is 1,2-bis(di-tert-butylphosphinomethyl) benzene and dba is (trans-trans-dibenzylideneacetone), has been prepared and characterized by variable temperature multinuclear NMR spectroscopy. The environment around palladium seems to be essentially trigonal planar, with small dihedral angles between P2Pd- and PdC2 planes. Tertiary phosphine ligands (PR3) play an extremely important role in the coordination chemistry of the late transition elements. They are important because they constitute one of the few series of ligands in which electronic and steric properties can be altered in a systematic and predictable way over a wide range by varying R. They also stabilize an exceptionally wide variety of metal species of interest to the organometallic chemist as their phosphine complexes (R3P)nM-L.